Complex Democracy
VI, 291 p. 18 illus.
Keywords: This book presents a state-of-the art collection of original contributions on democracy, addressing three related themes: the complexity of modern democracies and their structural diversity; coping strategies of democracies in times of crises; and current and potential trajectories and transformations of democracy. The first part of the book maps the democratic landscape by revealing the diversity of democratic political systems, through either comparative analysis or case studies on the specific nature of political and administrative systems in interest intermediation and identity construction. The second part presents articles that investigate the response of democracies to times of crisis, with an emphasis on political economies and policy processes within the European Union. The third part offers studies on democracies that explore their adaptive potential in the context of globalization, and in that of broader technical, institutional or cultural changes.